2012
DOI: 10.1007/s00439-012-1153-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of the MRC1 gene and the IFNG gene are associated with leprosy in Han Chinese from Southwest China

Abstract: Leprosy is an ancient infectious disease, with over 200,000 affected people (mainly in Asia and Africa) being registered annually. Genetic factors may confer susceptibility to this disease. In the present study, we genotyped 12 genetic variants of the MRC1 gene and the IFNG gene in 527 Han Chinese with leprosy and 583 healthy individuals from Yunnan, China, to discern potential association of these two genes with leprosy. In particular, we aimed to validate the recently reported association of MRC1 variant rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
(58 reference statements)
0
34
0
Order By: Relevance
“…In addition, several studies show a correlation between this sequence variant and invasive as well as pulmonary aspergillosis [116][117][118]. Finally, Sainz et al observe a correlation with susceptibility to aspergillosis in Candida colonization G [113] Recurrent vulvovaginal candidiasis G [114] Onychomycosis G [114] CLEC7A CD206 rs1926736 C > T Gly396Ser Tuberculosis C [122] Leprosy T [123,124] CD206 rs692527 T > C Unknown Leprosy C [124] CD206 rs34856358 C > T Unknown Leprosy T [124] PTX3 h2/h2 (G-A/G-A) Aspergillosis h2/h2 haplotype [125] PTX3 rs2305619 A > G Tuberculosis Haplotype (GAG) [126] PTX3 rs1840680 G > A Tuberculosis Haplotype (GAG) [126] Pseudomonas aeruginosa colonization Haplotype (GAG) [127] MBL rs1800450 rs5030737 rs1800451…”
Section: C-type Lectin Receptorsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, several studies show a correlation between this sequence variant and invasive as well as pulmonary aspergillosis [116][117][118]. Finally, Sainz et al observe a correlation with susceptibility to aspergillosis in Candida colonization G [113] Recurrent vulvovaginal candidiasis G [114] Onychomycosis G [114] CLEC7A CD206 rs1926736 C > T Gly396Ser Tuberculosis C [122] Leprosy T [123,124] CD206 rs692527 T > C Unknown Leprosy C [124] CD206 rs34856358 C > T Unknown Leprosy T [124] PTX3 h2/h2 (G-A/G-A) Aspergillosis h2/h2 haplotype [125] PTX3 rs2305619 A > G Tuberculosis Haplotype (GAG) [126] PTX3 rs1840680 G > A Tuberculosis Haplotype (GAG) [126] Pseudomonas aeruginosa colonization Haplotype (GAG) [127] MBL rs1800450 rs5030737 rs1800451…”
Section: C-type Lectin Receptorsmentioning
confidence: 93%
“…Very little is known about sequence variants in CD206 and susceptibility to infectious disease in humans. Nevertheless, sequence variant rs1926736 (Gly396Ser) in exon 7 of the MRC1 gene on chromosome 10 is suggested to be associated in susceptibility to leprosy and tuberculosis [122][123][124].…”
Section: • Mannose Receptormentioning
confidence: 98%
“…These samples had been analyzed for potential associations of other genes with leprosy in our previous studies1352. A total of 80 unrelated leprosy patients (38 lepromatous leprosy [LL] patients and 42 tuberculoid leprosy [TT] patients) with a family history of disease (each family has at least two leprosy patients) were collected from the Wenshan Prefecture, Yunnan Province.…”
Section: Methodsmentioning
confidence: 99%
“…affecting transcription factor binding sites or enacting other regulatory factor / mechanism, were estimated by referring to the RegulomeDB dataset (http://www.regulomedb.org/)36. All SNPs were genotyped in the cases and controls from the Yuxi Prefecture by using the SNaPshot assay (Table S7) as described in our previous studies2752 at the Kunming Biological Diversity Regional Center of Instruments, KIZ. For the NGS of the PARL, PINK1 and PARK2 genes in 80 leprosy patients from the Wenshan Prefecture, we used the same approach as described in our recent study53.…”
Section: Methodsmentioning
confidence: 99%
“…The MR C type 1 gene ( MRC-1 ) is located on chromosome 10p12 and consists of 30 exons. Several reports have shown that MRC-1 is associated with susceptibility to a subset of diseases, including asthma [19], sarcoidosis [20], and leprosy [21,22]. …”
Section: Introductionmentioning
confidence: 99%